Factors Favoring the Development of Chronic Subdural Hematoma After Traumatic Acute Subdural Hematoma in the Elderly. Issue 3 (March 2022) - Wasfie, Tarik; Fitzpatrick, Nicholas; Niasan, Mursal; Hille, Jennifer L.; Yapchai, Raquel; Hella, Jennifer; Barber, Kimberly; Brimmier, Alexis; Shapiro, Brian
Introduction: Traumatic acute subdural hematoma (TASDH) is by far the most common traumatic brain injury in elderly patients presented to the emergency department, and a number of those treated conservatively will develop chronic subdural hematoma (CSDH). The factors contributing to chronicity were not well studied in the elderly; therefore, we retrospectively analyzed our elderly patients with acute subdural hematomas to identify the risk factors which might contribute to the development of subsequent CSDH. Methods: A retrospective analysis of 254 patients with TASDH admitted between 2012 and 2016 to our level 2 trauma department in a community hospital was collected. Data include age, sex, comorbid conditions, CT findings, anticoagulant therapy, surgical interventions, disposition after discharge, and mortality. Data on those readmitted within the first 2 months with the diagnosis of CSDH were also studied (group A), and compared to those not readmitted (group B). Multiple logistic regression was used to determine the risk factors associated with readmission at P ≤ .05. Institutional review board approval was obtained for this study. Results: There were 254 patients who were admitted with TASDH, 144 male (56.7%) and 110 female (43.3%), with the mean age of 71.4 (SD ± 19.38) years. Only 37 patients (14.6%) went for surgery in their initial admission. A total of 14 patients (5.6%) were readmitted subsequently with the diagnosis of CSDH within two months of initial discharge (group A). Only four patients (28.5%) were on anticoagulant therapy and these patients went for emergency craniotomy for evacuation of hematoma. All 14 patients had a history of coronary artery disease and hypertension and only 5 (35.7%) were diabetic. Review of head CT on initial admission of those patients revealed 4 patients (28.5%) had multiple lesions and 4 (28.5%) had tentorial/falax bleeding and 4 (28.5%) had a shift. The initial size and thickness of the bleeding was 1.4-5 mm. The adjusted model identified diabetes, race, and initial disposition as significant risk factors ( P < .05). Conclusion: Risk associated with the transformation of TASDH to CSDH is difficult to assess in those group of elderly patients because of the small number; however, diabetes, race, and initial disposition to home pointed toward a risk for future development of CSDH and those patients should be followed clinically and radiographically over the next few months after discharge, particularly those on anticoagulant therapy.